1983
DOI: 10.2307/1937203
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐Related Foraging Behavior in Sequentially Hermaphroditic Hogfishes (Bodianus Spp.)

Abstract: I develop Schoener's proposal that the amount of activity time allocated to foraging can be sex related; males more often than females should minimize foraging time, and females should often be foraging-time maximizers. Sexual differences in foraging-time allocation may be small when male mating success is limited by available energy for maximizing sperm production.The foraging-time patterns of the sexes were examined in three sequentially hermaphroditic (protogynous) hogfishes in the genus Bodianus (Family La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
82
0
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 16 publications
9
82
0
1
Order By: Relevance
“…My data on activity time allocation in male and female Parapercis polyophthalma were concordant with the predictions of Schoener (1971), Hixon (1982Hixon ( , 1987 and Hoffman (1983) in that the amounts of time allocated to foraging and nonforaging activities can be sex related. Males spent much less time feeding and more time on territorial and social activities than did females, because males would be able to gain increased mating success by defending their territories, maintaining social dominance over females, and securing mates.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…My data on activity time allocation in male and female Parapercis polyophthalma were concordant with the predictions of Schoener (1971), Hixon (1982Hixon ( , 1987 and Hoffman (1983) in that the amounts of time allocated to foraging and nonforaging activities can be sex related. Males spent much less time feeding and more time on territorial and social activities than did females, because males would be able to gain increased mating success by defending their territories, maintaining social dominance over females, and securing mates.…”
Section: Discussionsupporting
confidence: 65%
“…Schoener (1971), Hixon (1982) and Hoffman (1983) predicted 3 general patterns of sex-related foraging behavior (or net energy gain) in mating systems where total male parental investment is lower than female investment, particularly in species showing no parental care. First, males tend to minimize foraging time when their reproductive success is limited more by the amount of time spent in social and mating activities than by foraging activities.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Bodianus rufus was recorded in three observation periods at 10 m and one at 15 m. Rooker et al (1997) found B. rufus less common at depths < 9 m, a distribution not consistent with the expected distribution if this predator was limiting the distribution of P. marmoreus. Bodianus rufus are territorial (Hoffman 1983) and additional observations indicated this species consistently frequented parts of the platform that offer some cover (where diagonal and vertical members meet). Such a territorial behavior would limit the potential for this predator to restrict a prey species on areas of the structure that are not a part of its territory.…”
Section: Discussionmentioning
confidence: 90%